Novel thermomechanical processing methods for achieving ultragrain refinement of low-carbon steel without heavy plastic deformation. Issue 1 (2nd January 2017) - Zhao, Lijia; Park, Nokeun; Tian, Yanzhong; Chen, Shuai; Shibata, Akinobu; Tsuji, Nobuhiro
ABSTRACT: Two novel two-step thermomechanical routes were developed to produce ultrafine-grained ferrite microstructures in a 10Ni–0.1C steel without high-strain deformation. Homogeneous ultrafine ferrite (UFF) structures having mean grain sizes down to 460 nm were fabricated by a total equivalent strain of 0.92 and exhibited high yield strength of 820 MPa with large uniform elongation of 10% and total elongation of 29%. The formation of UFF was attributed to two different phenomena, i.e. dynamic transformation from austenite to ferrite and dynamic recrystallization of ferrite. GRAPHICAL ABSTRACT: IMPACT STATEMENT Ultragrain refinement and remarkable strength-ductility properties can be achieved by controlling dynamic transformation and recrystallization in a thermomechanically controlled process without high-strain deformation.